PWE-044 A new one week high dose triple therapy for helicobacter pylori infection. (17th June 2017) - Sarras, K; Ghanad, E Ahadzadeh; Fong, S; Lim, TY; Logan, RP
Abstract : Introduction: Eradication of H.pylori infection cures duodenal ulcer disease; widespread use of eradication therapy for other indications and increasing prevalence of antibiotic resistance has resulted in efficacy of <75% for standard one week regimes, leading to more complex sequential, quadruple and hybrid treatment regimes.This prospective observational cohort study aims to evaluate the efficacy of a high dose one week triple therapy regime. Method: Patients undergoing OGD and found to be infected with H.pylori by CLO-test were considered for inclusion. Clinical data was extracted by review of electronic case notes. All patients were treated with omeprazole 20 mg bd, clarithromycin 500 mg tds and metronidazole 400 mg tds for 1 week by a single prescriber (RL) immediately after the end of the procedure. All patients were advised about possible side-effects and the importance of compliance in ensuring successful eradication. H.pylori status was confirmed prior to treatment by CLO-test +/- antral and corpus histology. Eradication was assessed by 13 C-Urea Breath Test ( 13 C-UBT) at least 6 weeks after the end of treatment. Results: From 2013–2016, 123 patients (male, n=82 (67%), mean age 52 year, range 18–85 years) with evidence of peptic ulcer disease (n=90 (73%)) severe oesophagitis (n=5, (4%)) or other indication for treatment were endoscoped and found to be H.pylori positive. Patients were mainly Caucasian (43%) or Afro-Caribbean (32%), and non-smokers (36%). Twenty seven patients did not attend for their follow-up 13C-UBT. For the 96 patients who had the UBT, the overall eradication rate was 90.6%. In previously untreated patients, eradication of H.pylori was achieved in 80/85 (94%). Of patients previously treated by their GP, 7/11 (64%) had successful eradication. Conclusion: This high dose one week H.pylori eradication regime was highly effective and may be an alternative to current more complex lengthy treatment options, but with the advantage of maximising the opportunity for patient compliance. References: . Logan RPH, Gummett PA, Misiewicz JJ, et al. A one week eradication regime for Helicobacter pylori. Lancet1991; 338:1249–52. . Malfertheiner P, Megraud F, O'Morain CA, et al. Management of Helicobacter pylori infection Maastricht IV/Florence Consensus Report. Gut2012; 61:646–64 . Li B-Z, Threapleton DE, Wang J-Y, et al. Comparative effectiveness and tolerance of treatments for Helicobacter pylori : systematic review and network meta-analysis BMJ2015;351:h4052 doi: 10.1136/bmj.h4052 Disclosure of Interest: K. Sarras: None Declared, E Ahadzadeh Ghanad: None Declared, S Fong Conflict with: Abbvie, Janssen, TY Lim: None Declared, R Logan: None Declared